Mating system in Pterocarpus macrocarpus Kurz in Thailand - Liengsiri, C.; Boyle, T.J.B.; Yeh, F.C. (1998)
The mating system in 11 natural populations of Pterocarpus macrocarpus Kurz in Thailand was investigated based on the mixed mating model using 16 isozyme markers. Single-locus outcrossing rates (tm) ranged from 0.719 to 0.959. Both ts and tm revealed a geographic pattern with western populations exhibiting higher outcrossing than eastern populations. Low estimates of outcrossing rates in eastern populations could be attributed to habitat characteristic, degree of disturbance, density, and distribution of flowering mature trees. Individual tree outcrossing rates (tmi) indicated that reduced population density associated with disturbance could result in low tm in some eastern populations